Calidad de servicio y satisfacción al cliente de la Empresa Quiero Mas SAC, Iquitos 2020 - Tambor Chota, Marilu (2022)
The research work entitled Quality of Service and Customer Satisfaction of the company I want more SAC, Iquitos 2020, aims to establish the relationship that exists between the quality of service and customer satisfaction in the company I want more SAC, Iquitos 2020. The study has a quantitative approach, descriptive-correlational type, non-experimental-cross-sectional design, whose population consisted of 45clients who fulfilled the specific conditions for the determined criteria. Fordata collection, the survey was used as a technique and the questionnaire as an instrument, with questions organized on a rating scale to show agreement or disagreement with the statements. For the information processing, the Microsoft Excel program was used, and the results expressed in tables and graphs. By analyzing the information collected, it was determined that 70% of customers felt comfortably satisfied with the services provided by the company and that it was better than the competition, and 77.5% highlighted the adequate infrastructure. And finally, it is appropriate to mention that positive responses were obtained that facilitated the analysis of the dimensions of reliability, security, empathy, performance, expectations and satisfaction levels, which facilitated the purpose of this research.